2012
DOI: 10.5137/1019-5149.jtn.5142-11.1
|View full text |Cite
|
Sign up to set email alerts
|

Large medial sphenoid wing meningiomas: long-term outcome and correlation with tumor size after microsurgical treatment in 127 consecutive cases

Abstract: AIm:We present the long-term outcomes as well as their correlation with tumor size in 127 consecutive patients harboring large MSWM after microsurgical treatment. mATeRIAL and meTHods:The retrospective analysis of clinical data and follow-up data of 127 microsurgical treated patients with MSWM was performed. The mean maximum diameter of tumors was 5.2cm (ranged 1.5-10.0cm).ResuLTs: 104 cases (81.9%) achieved gross total resection. There was no operative mortality. Detailed follow-up data was available in 120 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 25 publications
0
18
1
Order By: Relevance
“…[7] Histopathological examination showed the most common type was WHO Grade I Mesothelial meningioma in 23 cases (48.9%) as reported by many authorities. [11,14,17] but we had three cases of atypical meningioma which different from Nakamura et al who did not report any cases of atypical meningioma [14] In patients long-term prognosis regarding the quality of life: Over all the mean KPS score for the patients in the study was 86.2 (ranged from 60 to 100) at 1 year after surgery, which was 74.5 at 10 days after surgery. While AbdelAziz et al stated excellent outcomes 38 patients, with a KPS score > 90 in 89% of their cases 1 year after surgery [1]and Liu et al showed In 120 MSWMS cases mean KPS was 83.5 at 10 days after surgery then improved to be 90.6 as mean KPS (ranged from 60 to 100) 12 months after [11].so our results may goes with international data because of advanced microsurgical techniques, learning curve with preservation of perforators whenever possible and appropriate decision making according to patient condition.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…[7] Histopathological examination showed the most common type was WHO Grade I Mesothelial meningioma in 23 cases (48.9%) as reported by many authorities. [11,14,17] but we had three cases of atypical meningioma which different from Nakamura et al who did not report any cases of atypical meningioma [14] In patients long-term prognosis regarding the quality of life: Over all the mean KPS score for the patients in the study was 86.2 (ranged from 60 to 100) at 1 year after surgery, which was 74.5 at 10 days after surgery. While AbdelAziz et al stated excellent outcomes 38 patients, with a KPS score > 90 in 89% of their cases 1 year after surgery [1]and Liu et al showed In 120 MSWMS cases mean KPS was 83.5 at 10 days after surgery then improved to be 90.6 as mean KPS (ranged from 60 to 100) 12 months after [11].so our results may goes with international data because of advanced microsurgical techniques, learning curve with preservation of perforators whenever possible and appropriate decision making according to patient condition.…”
Section: Discussionmentioning
confidence: 66%
“…during the series upgrade we adopt more skull base bone removal to minimize brain retraction, minimize coagulation to reduce the incidence of new neurological deficit. Many paper mentioned these complications in similar surgeries for MSWM as Nakamura et al, Czernicki et al, Bassiouni et al, Hao, Liu et al [3,7,8,11,14] may be it appeared in ours and in Nakamura et al study due to presence of larger tumours that extend posteriorly and superiorly wit adherence to MCA or ACA perforators or to the MCA or ACA adventitia [2]. Thus also explain the presence of two cases of cerebral infarction which was evident clinically & radiologically.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations